I see you - Mackintosh, Clare (Berkley, 2017)
"The author of the smash bestseller, I Let You Go, propels readers into a dark and claustrophobic thriller, in which a normal, everyday woman becomes trapped in the confines of her normal, everyday world... Every morning and evening, Zoe Walker takes thesame route to the train station, waits at a certain place on the platform, finds her favorite spot in the car, never suspecting that someone is watching her... It all starts with a classified ad. During her commute home one night, while glancing throughher local paper, Zoe sees her own face staring back at her, a grainy photo along with a phone number and listing for a website called findtheone.com. Other women begin appearing in the same ad, a different one every day, and Zoe realizes they've becomethe victims of increasingly violent crimes--including rape and murder. With the help of a determined cop, she uncovers the ad's twisted purpose...a discovery that turns her paranoia into full-blown panic. For now Zoe is sure that someone close to her hasset her up as the next target. And now that man on the train--the one smiling at Zoe from across the car--could be more than just a friendly stranger. He could be someone who has deliberately chosen her and is ready to make his next move